Mobile Monopoly Game: REV-OPOLY ON THE GO - Jian, Goh Jun; no, Noradila (Multidisciplinary Applied Research and Innovation, 2023)
REV-OPOLY ON THE GO is a mobile monopoly game set during the impending technological revolution. In comparison to the traditional approach of self-revision, the goal of REV-OPOLY ON THE GO is to improve students' understanding in terms of their capacity to make explicit references to past learning and show and apply information in a game-based setting. REV-OPOLY ON THE GO is a quiz that assesses students' understanding of the emerging technological revolution, which is covered in one of the University Utara Malaysia courses. Incorporating gaming components is supposed to increase students’ interest in the course while also enhancing their comprehension. The game may be used as a review tool to remind students of the theme of the emerging technological revolution, which is discussed during lectures. In the game, the student will compete against the bot to buy the technologies by answering the questions. To prevent the bot from winning the game, students are required to know the topic of the subject. REV-OPOLY ON THE GO allows students to have a more relaxed learning experience while still following the same syllabus and having fun.